“FRAUD” IN THE MANAGEMENT OF FUNCTIONAL LITERACY PROGRAM - Alil Mafahir; Siti Musyarofah; Prasetyono Prasetyono (JAFFA, 2018)
The aim of this research is to identify the pattern of fraud in the management of functional literacy program. This is a descriptive qualitative research. This research employed primary data with interview, institutional document analysis, and observation as the method of data collection. The findings of this research suggest that there are some fraud patterns found in the management of functional literacy program i.e. (1) the proposal creation as an administrative formality (2) the reduction of the learning duration (3) the reduction of the tutor’s transportation fees (4) the reduction of the stationery procurement budget.